PENGARUH RATING DAN REVIEW TERHADAP KEPUASAN PEMBELIAN ONLINE PADA E-COMMERCE SHOPEE DI KALANGAN SISWA SMA - Salwa Putri Yusmanta; kuswanto . (Journal MISSY (Management and Business Strategy), 2026)
The development of digital technology has driven an increase in online shopping activities through e-commerce, including the use of the Shopee application among high school students. In making transactions, consumers generally utilize rating and review features as considerations before purchasing a product. This study aims to analyze the impact of ratings and reviews on online purchasing satisfaction among grade XII students of SMAN 1 Sukodadi. Using an associative quantitative method, this study analyzed data from 50 respondents who responded to 20 statement items. The data analysis process was carried out using the IBM SPSS Statistics 25 application. Based on the test results, all instrument items were declared valid because they had a significance value of 0.000, which was below the threshold of 0.05. In addition, the reliability test produced a Cronbach's Alpha coefficient of 0.771, thus the instrument was proven reliable for use. The t-test showed that ratings had a significant effect on purchasing satisfaction with a significance value of 0.001 and reviews of 0.004. In addition, the F-test obtained a significance value of 0.000 with a coefficient of determination (R²) of 0.701.